Liposomes Advances and Perspectives - Catala, Angel (IntechOpen, 2019)
Liposomes have received increased attention in recent years. Nevertheless, liposomes, due to their various forms and applications, require further investigation. These structures can deliver both hydrophilic and hydrophobic drugs. The preparation of liposomes results in different properties for these systems. In addition, there are many factors and difficulties that affect the development of liposome drug delivery structures.The purpose of this book is to concentrate on recent developments in liposomes. The articles collected in this book are contributions by invited researchers with long-standing experience in different research areas. We hope that the material presented here is understandable to a broad audience, not only scientists but also people with a general background in many different biological sciences. This volume offers up-to-date, expert reviews of the fast-moving field of liposomes and is divided in two major sections: 1. Introduction; 2. Liposomes general properties